Controlling the rates of reductively-activated elimination from the (indol-3-yl)methyl position of indolequinones - Everett, SA; Naylor, M; Barraja, P; Swann, E; Patel, K; Stratford, M; Hudnott, A; Vojnovic, B; Locke, R; Wardman, P; Moody, C (2001)
A series of substituted 3-(4-nitrophenyloxy)methylindole-4,7-diones (Q) were synthesised. The effects of substitution patterns on the indole core on rates of elimination of 4-nitrophenol as a model for drug release following fragmentation of a phenolic ether linker were studied. After reduction to either the radical anion (Q·-) or hydroquinone (QH2) elimination of 4-nitrophenol occurred from the (indol-3-yl)methyl position. The half-lives of Q·- radicals at [O2] ≈ 5 μmol dm-3, typical of tumour hypoxia, were t1/2 ≈ 0.3-1.8 ms, the higher values associated with higher reduction potentials. Half-lives for the autoxidation of the QH2 were markedly longer at the same oxygen concentration (t1/2 ≈ 8-102 min) and longer still in the presence of 4 μmol dm-3 superoxide dismutase (t1/2 ≈ 8-19 h). Although the indolequinones were able to eliminate 4-nitrophenol with high efficiency only Q·- radicals of the 3-carbinyl substituted derivatives did so with sufficiently short half-lives (t1/2 ≈ 41-2 ms) to compete with electron transfer to oxygen and therefore have the potential to target the leaving group to hypoxic tissue. The hydroquinones are not sufficiently oxygen sensitive to prevent the elimination of 4-nitrophenol (t1/2 ≈ 1.5-3.5 s) even at oxygen concentrations expected in normal tissue. By incorporating electron rich substituents at the indolyl carbinyl position it is possible to control the rate of reductive fragmentation. This may prove an important factor in the design of an indolequinone-based bioreductive drug delivery system.